AB0094 Possitive effetcs of chiropractic manipulation on subchondral bone mineral density, cartilage damage and synovial inflammation in osteoarthritic rabbits. (12th June 2018) - Conesa, F.M.; Fujikawa, R.; Mediero, A.; Gratal, P.; Mulero, F.; Herrero-Beaumont, G.; Largo, R.; Ortega-de Mues, A.
Abstract : Background: Osteoarthritis (OA) is a degenerative joint disease characterised by the degradation and inflammation of cartilage and synovium with bone damage. Different approaches that decrease subchondral bone remodelling during OA have demonstrated to improve cartilage damage and synovial inflammation. Chiropractic is a therapeutic approach focused on the diagnosis, treatment and prevention of musculoskeletal disorders. Chiropractic manipulation (CM) is essentially manual, allowing the chiropractor to restore the normal range of motion and function of the joints, muscles, and ligaments. We have previously observed that CM is able to increase subchondral bone mineral density (BMD) in an experimental model of osteoporosis 1 . Objectives: To evaluate if CM could prevent the subchondral BMD alterations induced by OA, in association to an improvement in synovial membrane inflammation and cartilage damage in an OA model in rabbits. Methods: Ten male New Zealand rabbits were submited knee surgery to induce OA by transection of anterior cruciate ligament. CM was performed using the chiropractic adjusting instrument ActivatorV 3 times a week during 8 weeks as follows: Force 2 setting was applied onto the tibial tubercle of the rabbit right hind limb (CM-OA group), at an angle of 90°, whereas the corresponding left hind limb received a false manipulation (FM-OA group) consisting of ActivatorV firing in the air and touching the tibial tubercle. Three healthy animals were used as controls. Following sacrifice, tibiae and femora were removed for mCT and histological evaluation. Synovial inflammation was evaluated by Krenn's score and the protein presence of VEGF, MMP3 and CollagenVI in the synovial membrane was evaluated by western blot. Results: In the OA rabbits, subchondral BMD decreased in relation to control animals ( OA 4729±193 vs Control 5181±209 mg/cc ), been partially reversed in the tibiae of OA rabbits with CM ( TM-OA 5055±216 vs FM-OA 4404±170 mg/cc ). Subchondral trabecular bone structural parameters were analysed by microCT and a significant decrease of bone volume/trabecular volume (BV/TV), trabecular number (TbN) and trabecular thickness (TbTh) was observed in the OA rabbits, while trabecular separation (TbS) increased compared to control animals. TM-OA group showed a significant improvement of these parameters compare to FM-OA group. TM-OA had lower cartilage damage compare to FM-OA ( TM-OA 4±0, 67 AU vs FM-OA 8±1, 25  AU). TM-OA synovial membranes presented a total Krenn score lower than FM-OA joints ( TM-OA 3±0, 35 vs FM-OA 4.5±0, 38  AU). OA synovial membranes showed higher levels of CollagenVI respect to control ones; TM-OA synovial membranes presented less expression of CollagenVI than FM-OA group ( TM-OA 1.4±0, 13 vs FM-OA 2.2±0, 3  AU), been this associated with a decrease of both MMP3 ( TM-OA 1.2±0, 1 vs FM-OA 1.7±0.2  AU) and VEGF ( TM-OA 1.2±0.14 vs FM-OA 1.9±0.26  AU). Conclusions: These results support the hypothesis that CM may ameliorate subchondral BMD alterations induced by OA, in association to an improvement on synoviopathy and cartilage degradation. Reference: [1] López-Herradón A, et al. Impact of Chiropractic Manipulation on Bone and Skeletal Muscle of Ovariectomized Rats.CalcifTissueInt2017;101(5):519–529. Disclosure of Interest: F. Conesa: None declared, R. Fujikawa: None declared, A. Mediero Grant/research support from: CP15/00053 PI16/00991, P. Gratal: None declared, F. Mulero: None declared, G. Herrero-Beaumont Grant/research support from: PI16/00065, R. Largo Grant/research support from: PI15/00340, A. Ortega-de Mues: None declared